Pembelajaran untuk Membangun Percaya Diri Anak Usia 5-6 Tahun Melalui TV Sekolah TK Islam Al-Azhar 1 Kebayoran Baru - Nurbani, 1. Babay; Watini, Sri; Hulailah Istiqlaliyah (STIT Fatahillah, 2022)
Children's self-confidence needs to be built from an early age because not all children have the confidence to show their abilities. This article aims to describe learning to use school TV to develop the confidence of children aged 5–6 years. The method used in this article is descriptive-analytic, namely by narrating and analyzing the learning process, which is then used as content for school TV. The primary data sources in this article are the students of group B3, which consists of 11 boys and 6 girls. The findings in this study show that school TV learning is carried out through collaboration between teachers and parents, teachers prepare learning content that is broadcast, and parents are involved to motivate students to participate in learning. Activities are carried out as usual in the classroom, from start to finish. The conclusion of this research is that students are very happy and proud to participate in learning that is broadcast on school TV, thus motivating students to be confident, enthusiastic, and creative in participating in learning.